Influence of portfolio management in decision-making - Baptestone, Rolney (2018)
This research aims to demonstrate how portfolio management influences the decision-making process in the projects of a financial organization. And to achieve this goal was used the single case study method. In order to reach this goal, the study began by means of bibliometric research on the subject of portfolio management and subsequent bibliographic research on the theme, decision making. Next, the relationships between portfolio management and decision making were studied. The results of the data collected confirmed the relationship between "the use of the project identification process in portfolio management to influence decision making" in order to add value to the business. It is also possible to demonstrate moderately that "the use of criteria for project selection influences the consequences of decision making", helping in the strategic management of the organization. One of the academic contributions was to note a migration of the portfolio management process, such as a tool that only controls the projects that will compose the portfolio of an organization, for a process that aims at a direct alignment with the strategic management of the organization. Regarding the practical implications, it was verified the importance of portfolio analysis for decision making, to the detriment of the evaluation of only one project. Taking into account the profitability and the return on investment of the projects, as the most important aspects for a decision making.